2021
DOI: 10.1038/s41598-021-88059-0
|View full text |Cite
|
Sign up to set email alerts
|

Color-dependent changes in humans during a verbal fluency task under colored light exposure assessed by SPA-fNIRS

Abstract: Light evokes robust visual and nonvisual physiological and psychological effects in humans, such as emotional and behavioral responses, as well as changes in cognitive brain activity and performance. The aim of this study was to investigate how colored light exposure (CLE) and a verbal fluency task (VFT) interact and affect cerebral hemodynamics, oxygenation, and systemic physiology as determined by systemic physiology augmented functional near-infrared spectroscopy (SPA-fNIRS). 32 healthy adults (17 female, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 102 publications
1
25
0
Order By: Relevance
“…For small apartments, high‐chroma colours may produce a sense of depression, which has been verified in some extreme environments, such as the internal environment of a space station or a submarine 75,76 . A large number of studies have found that colours with high chroma or strong contrast can cause severe visual stress, which in turn induces negative emotions, because high chroma increases the cerebral oxygenation of the visual cortex of the brain 70,77,78 . Mahnke believes that the colour design in a man‐made environment must refer to the colour matching of a natural scene.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For small apartments, high‐chroma colours may produce a sense of depression, which has been verified in some extreme environments, such as the internal environment of a space station or a submarine 75,76 . A large number of studies have found that colours with high chroma or strong contrast can cause severe visual stress, which in turn induces negative emotions, because high chroma increases the cerebral oxygenation of the visual cortex of the brain 70,77,78 . Mahnke believes that the colour design in a man‐made environment must refer to the colour matching of a natural scene.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with some other studies. Colours with high chroma will strongly affect a human's visual perception and physiological response, especially when performing some highly mental workload tasks (such as visual tracking, comparison tasks 69,70 ), and physiological representations will react strongly (eg, physiological signs such as brain cerebral oxygenation, HRV, and galvanic skin response 49 ). Such colours have a promoting effect on task performance 69 but being in such an environment for a long time will cause mental tension and even negative emotions such as depression and anxiety 71,72 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we controlled for various environmental confounders. fNIRS results must be interpreted with caution as they are highly variable, due to differences caused by the melatonin concentration in the skin ( 82 ) and a number of missing data due to low quality of signal. Finally, in this experiment only the momentary changes in mood and brain activity were examined, and only longitudinal data would allow us to determine how long the beneficial effects we observed here can be sustained over time.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is known that some cortical regions and the autonomic nervous system are concurrently activated [ 51 ], especially during cognitive tests [ 52 , 53 ]. Furthermore, the IRT signal could be used also to assess and correct autonomic contaminations in the fNIRS signal [ 29 , 54 , 55 , 56 ]. In fact, it should be stressed that IRT recordings can provide information regarding the breathing rate [ 57 , 58 ] and the superficial perfusion [ 59 ] that could influence the fNIRS recordings.…”
Section: Discussionmentioning
confidence: 99%